Design Joins the Battle Against Sickle‐Cell Disease. (16th August 2013) - Crosby, Lori E.; Joffe, Naomi E.; Dunseath, Linda A.; Lee, Rachel
<x xml:space="preserve">Abstract</x> A design‐thinking approach at Cincinnati Children's Hospital Medical Center helps kids with sickle‐cell disease transition into managing their disease as adults.